The Use of Interpretative Phenomenological Analysis in History Education - Oltar, Selly Afrida; Marta, Nur’aeni; Kurniawati , Kurniawati (Green Publisher Indonesia, 2025)
Interpretative Phenomenological Analysis (IPA) is a qualitative research methodology used to understand the subjective reality of informants through their personal interpretations of life experiences and the meanings they derive from those experiences (Smith, 2011). Initially, IPA was widely used in psychological studies. Over time, and with the development of knowledge, IPA has been adopted in other fields, including education. This article seeks to describe the use of IPA by researchers in the study of history education. Specifically, the author explores aspects of collective national emotions, particularly nationalism, experienced and embedded in high school students during and after their history learning, especially in local history. I attempt to present a small example that IPA can indeed be very effective in describing students' learning experiences and the affective outcomes (emotions and attitudes) from learning that should ideally become ingrained within them. Regarding history education, the involvement of collective emotions such as nationalism should be embedded in students both during and after the learning process, ultimately shaping the national character of all students even after they have graduated. The results of this study indicate that using the IPA method in this research is quite meticulous and produces a significant amount of required data. It shows that high school graduates in Papua do not perceive local history learning as interesting and that it minimally evokes emotions, thus failing to foster or strengthen their Indonesian nationalism.